Representação, informação e deliberação no processolegislativo estadual - Marta Mendes da Rocha (2011)
The central theme of this thesis is the relationship between representation, deliberation and information, more specifically, the space of deliberation in decision-making process in parliament. The central problem of research refers to a subject little studied, either in the field of legislative studies, either within the theory of deliberative democracy: the space for deliberation in the legislative process and the conditions that favor a decision process with a high volume of informed deliberation. The neglect of this issue has left a gap in contemporary democratic theory when one considers that the deliberation is (or should be) a dimension component of the legislative process, along with other forms of political interaction and decision-making methods. The central hypothesis of this research suggests there is an association between an organization's informational Legislative and deliberative process characterized by a higher volume of informed deliberation. To verify the hypothesis was made a comparative analysis of decision processes in the Legislative Assemblies of Minas Gerais and Bahia in 2007 and 2008. The study involved the use of quantitative techniques and qualitative research and analysis on decision making in all its phases, focusing on the stage of consideration by committees of merit. From evidence to show that the Legislative Assemblies of Minas Gerais has many traits of an informational organization, which does not appear in the Assembly of Bahia, it was hoped that the decision process on the first involves a larger volume of deliberation and that this would more qualified in relation to the decision process in Bahia Assembly. The search allows perceive the gains in terms of legislative drafting in presence and availability of information resources for all members of the Legislature in the Legislative Assembly of Minas Gerais. However, the study revealed that although an informational organization may be necessary to a high volume of informed decision making process, it is not enough. Other factors may influence the pattern of interaction between parliamentarians and their willingness to engage in study and discussion of the projects assessed.